THE EFFECT OF BEHAVIORAL CONTROL, ORGANIZATIONAL COMMITMENT, SELF KEFFICACY, AND MORAL INTENSITY ON WHISTLEBLOWING INTENTION - Krisdayanti, Ni Putu Meita; Ratnadi, Ni Made Dwi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Village Credit Institutions (LPD) play a strategic role in helping micro and small businesses and rural communities. However, several problems such as cases of fraud still occur, so a whistleblowing system is important to detect and prevent unethical practices. This study attempts to gain insight into the influence of behavioral control, organizational commitment, self-efficacy, and moral intensity on whistleblowing intentions. Researchers looked at 75 employees from 9 LPDs in South Kuta District. Probability sampling is utilized in the sampling procedure with a simple random sampling technique, and data is gathered via a survey questionnaire. Data analysis using multiple linear regression shows that behavioral control, organizational commitment, self-efficacy, and moral intensity have a favorable impact on the intents of whistleblowers. Implications related to the theory of planned behavior show that whistleblowing intentions are influenced by the belief that reporting violations helps maintain the integrity and reputation of the organization. This research can be input for LPDs in South Kuta District.